2021
DOI: 10.1097/as9.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Method for Estimating the Carbon Footprint of Disposable Minimally Invasive Surgical Devices

Abstract: Objective: To propose a standardized methodology for estimating the embodied carbon footprint (CF) of disposable minimally-invasive surgical devices (MISDs) and their application in new benign prostatic hyperplasia (BPH) MISDs. Summary of Background Data: The estimation of the CO2e emissions of disposable surgical devices is central to empowering the healthcare supply chain. Methods: The proposed methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…Finally, for the surgery itself, surgical packs of sterile instruments are frequently opened before surgery begins 50 . Eighty per cent of surgical solid waste is generated before the patient enters the operating theatre, and most of this waste is associated with packaging 51 , 52 . There is a lack of robust evidence on how much waste could be avoided if sterile pack openings were delayed until the start of surgery.…”
Section: Health-care Carbon Footprintmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, for the surgery itself, surgical packs of sterile instruments are frequently opened before surgery begins 50 . Eighty per cent of surgical solid waste is generated before the patient enters the operating theatre, and most of this waste is associated with packaging 51 , 52 . There is a lack of robust evidence on how much waste could be avoided if sterile pack openings were delayed until the start of surgery.…”
Section: Health-care Carbon Footprintmentioning
confidence: 99%
“…In England, 80% of operating theatre waste is generated preoperatively, 90% is misallocated and 40% is potentially recyclable. Thus, implementing and disseminating the recycling process in the operating theatre and beyond is crucial 52 , 63 , 80 .…”
Section: Sustainable Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon footprint for disposable operating room supplies has been estimated between 0.07 (for transurethral prostate surgery) and 505 (for robotic hysterectomy) kilograms of carbon-dioxide equivalent, the latter of which is comparable to driving more than 1,500 miles in an average petrol car. 28,29 Reducing the use of laparoscopic disposable supplies can lower carbon-dioxide emissions from supply manufacturing, transport, and waste disposal. Importantly, reusable laparoscopic supplies also have economic and environmental costs, related to supply sterilization and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…These are packaged in plastic and nondegradable material. The industry should develop reusable devices packaged in recyclable and environmentally friendly materials b) Reduce Waste Production at All Steps in the Care Pathway (before, during, and after an IP Procedure) A recent study proposed a simplified method to estimate the carbon footprint of disposable surgical devices in urology and showed that up to 86% of GHG emissions were attributed to disposable packaging and user manuals [17]. Gastroenterology procedures are very similar to IP procedures.…”
Section: Reduce Waste A) Increase Waste Segregationmentioning
confidence: 99%